The extended modified Logvinovich model: Application to the water entry of two-dimensional wedges - Yang Zhang; Se-Myong Chang; Deuk-Joon Yum (International Journal of Naval Architecture and Ocean Engineering)
A planing craft is one of the most commonly used types for small high-performance vessels since it helps to mitigate the severe viscous friction between the ship hull and water. Therefore, it is essential to develop methods for quickly and accurately estimating the running attitude during the early design phase and in actual operational conditions. We propose the Extended Modified Logvinovich Model (EMLM) for water entry to address the flow separation problem when a wedge-shaped hull enters the free surface during motion. Utilizing a two-dimensional approximation, we analyzed the fundamental potential flow through mathematical techniques for unsteady flow. As a verification, we calculated the dynamic vertical force coefficient compared with CFD(computational fluid dynamics) based on BEM(boundary element method) and an analytic similarity solution, where the results demonstrated good agreement with experimental data for validation.